2022
DOI: 10.1155/2022/3182368
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic Polypeptide D7 Protects Bone Marrow Mesenchymal Cells and Promotes Chondrogenesis during Osteonecrosis of the Femoral Head via Growth Differentiation Factor 15-Mediated Redox Signaling

Abstract: Osteonecrosis of the femoral head (ONFH) is a debilitating disease that is closely associated with the clinical application of high-dose glucocorticoids. Elevated oxidative stress contributes to the pathophysiological changes observed in ONFH. The lack of effective treatments besides surgical intervention highlights the importance of finding novel therapeutics. Our previous studies demonstrated that D7, a cyclic polypeptide, enhances the adhesion, expansion, and proliferation of bone marrow mesenchymal stem ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 51 publications
(64 reference statements)
0
4
0
Order By: Relevance
“…Currently, available studies cannot fully reveal the relationship between ferroptosis and apoptosis, and more research is needed in this area. Previous studies reported that Dex induces the imbalance of redox homeostasis [ 37 ]. Furthermore, ferroptosis isdriven by lethal lipid peroxidation, a consequence of cellular metabolism and imbalanced redox homeostasis [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, available studies cannot fully reveal the relationship between ferroptosis and apoptosis, and more research is needed in this area. Previous studies reported that Dex induces the imbalance of redox homeostasis [ 37 ]. Furthermore, ferroptosis isdriven by lethal lipid peroxidation, a consequence of cellular metabolism and imbalanced redox homeostasis [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several signaling pathways are involved in the process of macrophage polarization (8,(173)(174)(175)(176)(177)(178)(179). Various ligands, receptors, transcription factors, and other factors cooperate closely to ensure the precise regulatory capacity of macrophages (8).…”
Section: Regulatory Mechanisms Of Macrophages In Almentioning
confidence: 99%
“…And the modified functional scaffold demonstrated that the adhesion, spreading, and proliferation of BMSCs were enhanced compared with unmodified (β‐TCP) in vitro. And D7 were demonstrated to exhibit the protective function to BMSCs against dexamethasone‐induced ONFH, which revealed its potential therapeutic effects (Chen et al., 2022).…”
Section: Current and Futural Application In Food Productionmentioning
confidence: 99%